Determination And Morphology Of Leaf Starch Granules From Trunking And Non-Trunking Sago Palm Leaves - Paramjit Kaur, D/O Suk Dave Singh. (Universiti Malaysia Sarawak (UNIMAS), 2009)
Sago palms which are widely distributed in Malaysia are from the genus Metroxylon. The present study was carried out to determine the morphological structure of the starch granule which is found in the leaves of tnmking and non-trunking sago palm. The structure of starch granule obtained from both the trunking and non trunking sago paffi1leaves were compared. The leaves were cleaned and homogenized using extraction medium containing MOPS, ethylene glycol and EDTA. The homogenate were then vortexed, filtered, centrifuged, washed and finally left at room temperature for drying. The dried starch granules from both the trunking and non-tnmking sago palm leaves were observed under scanning electron microscope (SEM). The starch granules structure observed from both the trunking and non-trunking sago palm leaves are oval and truncated with the size range of I ~till 10 f.UI1. Therefore, there is no observable difference between the structure of starch granule from trunking and non-tnmking sago palm leaves. Besides that, another method of extraction of starch granules using glass wool did not show any results as no starch granules were observed.